Evaluación de la función gerencial de los rectores de los colegios técnicos del cantón Santa Rosa y la organización institucional período 2011-2012. Propuesta alternativa de un programa gerencial basada en la teoría de la complejidad y su relación con los estándares internacionales de calidad. - Matamoros Veléz, Ricardo Anfonio (2015)
The educational administration of the different technical schools in the canton Santa Rosa , do not meet the quality standards of education of Ecuador and the world. Reason why this research was conducted based on the existing need to develop a management program that offers to improve the management function while coadyugar the development of the area, causing great impact on society , this research is based on the theory of complexity give guidelines for the structure to have a sense of belonging and relevance in actions for the transformation of educational institutions and consolidate their progress .